Ricerca e caratterizzazione diVibrio parahaemolyticusin molluschi bibalvi vivi della Regione Sardegna - MARCEDDU, Marta (Università degli studi di Sassari, 2015)
During 2013, 1079 mollusk samples collected from Sardinia ASLs (754 for Monitoring and 325 for market surveillance) were analyzed by IZS of Sassari. Samples were oysters (Crassostrea gigas,Ostrea edulis), clams (Tapes philippinarumanddecussatus) and mussels (Mytilus galloprovincialisandedulis). Samples were analyzed forV. parahaemolyticusby the ISO/TS 21872-1:2007. Strains were tested by PCR for the presence ofV. parahaemolyticusspecies-specific genes (toxR) and to detect the virulence genes (tdhandtrh). Group specific (GS)-PCR method, based on the sequence variation inToxRSgene, was also performed to detect the pandemic clone in correlation withtdhgene.V. parahemolyticusprevalence was 3.5% (38/1079). between positive samples, 35 (92.1%) were for Monitoring and 3 (7.9%) for official controls. tdh gene was identified In 5 (13%) samples, but there was no correlation withtoxRSgenes. Furthermore,trhgene was detected in 10 (26.3%) samples.V. parahaemolyticusis responsible of emerging public health problems. Reg. CE 2073/2005 does not fix specific criteria, however, recommend the application of good hygienic practices.V.parahaemolyticusprevalence is low. However, such results confirm that it is necessary acquire more knowledge aboutV. parahaemolyticusin Sardinia marine seawater. It would be appropriate to include this microorganism in the surveillance systems for gastrointestinal diseases and in monitoring programs in mollusk collection areas.